Engagement and Consumption Behavior in Gacha Games: A PLS-SEM Study on Generation Z in Indonesia - Yuda Priyangga, Raka; Salehudin, Imam (Journal of Games, Game Art, and Gamification, 2025)
Gacha games have gained popularity as a free-to-play model, sparking increasing interest in player consumption behavior. Understanding this behavior is critical, as it has implications for player retention, monetization strategies, and potential risks of compulsive spending. While existing studies largely focus on purchase intention, other consumption behaviors—such as co-production, community engagement, word-of-mouth, and recruitment—remain underexplored. This study aims to examine how player engagement in Genshin Impact affects these various forms of consumption behavior. Focusing on Generation Z in Indonesia—a digitally native cohort deeply immersed in mobile gaming—the research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 344 respondents who have played the game for at least six months. Findings reveal that satisfaction through games, game personalization, and game social interaction significantly influence player engagement, which in turn positively affects multiple dimensions of consumption behavior. These results offer practical insights for game developers and marketers seeking to foster sustainable and ethical engagement strategies in gacha games.